Evaluación de la respiración de sedimentos en estanques para el cultivo de litopenaeus vannamei - Heras Márquez, Nancy Isabel (2013)
Shrimp farming is currently one of the fastest growing activities in the world. The soil is a key factor in aquaculture production, considering that certain conditions in the water and soil within shrimp ponds can affect the farmed animal. This research was conducted in the shrimp farm Armatecsa SA, located in the Canton Naranjal, of the Guayas Province, Matorrillo sector, and had the following objectives: 1) To quantify the sediment respiration in semi-intensive ponds for the culture of Litopenaeus vannamei, 2) To quantify the concentration of organic matter in the sediment during a grow-out season, 3) To determine the relationship between respiration of sediment and organic matter. Based on the results from this research, we can conclude the following: The sediment respiration expressed as mg O2/m2 in the three ponds surveyed was equal in both the inlet, middle part and outlet. While when being expressed as mg O2/m2/h only show significant statistical difference at the inlets of the ponds. Organic matter (expressed as %) in the three ponds shows no statistical difference in the inlets and outlets, while at the middle part statistical difference was found, which can be attributed to a lower organic matter accumulation rate in this area of the ponds, usually due to water exchange/movement (and removal of sediment) during this process. Additionally, it was observed how the pond management influences the accumulation and respiration of the sediment along the farming period, since the results indicate that there is a correlation (r2 = 0.77) between the concentration of organic matter and sediment respiration. Specifically it was noted that the higher the organic matter accumulation the higher the respiration rate in the sediment, mainly at the inlets and outlets of the surveyed ponds, variations probably due to the different types of organic matter and their decomposition rate and/or resistance to decay.